The Methodology of Abū Dāwūd in Assessing Mursal Hadith: An Analytical Study of Bāb al-Nikāḥ in Kitāb al-Marāsīl - Muhammad Fatkhun Niam; Hifdul Ulum; Ahmad Mukhlish Sirojuddin; Agus Salim; Khamim Khamim (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to examine the methodology of Abū Dāwūd in evaluating mursal traditions in Kitāb al-Marāsīl, particularly in Bāb al-Nikāḥ. The research focuses on sanad criticism, the technical expressions employed by Abū Dāwūd in assessing narrations, and the criteria for accepting and rejecting mursal traditions. This research employs a qualitative method based on library research with a descriptive-analytical approach. The primary sources are Kitāb al-Marāsīl and Sunan Abī Dāwūd, while secondary sources include works on ʿulūm al-ḥadīth, rijāl al-ḥadīth, commentaries, and other relevant academic literature. The findings reveal that Abū Dāwūd adopted a moderate position regarding mursal traditions. He neither rejected them absolutely, as some hadith scholars did, nor accepted them unconditionally. Mursal traditions were accepted when narrated by trustworthy senior tābiʿīn, supported by shawāhid or mutābiʿāt, and in accordance with established legal principles. Conversely, mursal traditions narrated by junior tābiʿīn, weak narrators, mudallis transmitters, or narrations lacking corroboration were generally rejected. In his sanad criticism, Abū Dāwūd employed technical expressions such as hādhā mursal, hādhā yuʿrafu mursalan, wa al-ṣaḥīḥ annahu mursal, and al-wahm min fulān to explain the status of narrations and identify defects in the chain of transmission. This study also finds corroborative narrations (mutābiʿ) for several mursal traditions in Bāb al-Nikāḥ, especially the tradition “idhā jā’akum man tarḍawna dīnahu wa khuluqahu fa ankiḥūhu,” thereby strengthening their validity according to Abū Dāwūd’s methodological standards.